Comparison of Anti-Bacterial Activity of Methanol Extract and Non-Polar Fraction of Macroalgae Sargassum sp. - Wibowo, Adi Tri; Widyastuti, Sri; Prasedya, Eka Sunarwidhi; Mukhlishah, Neneng Rachmalia Izzatul; Pangestu, Kukuh Waseso Jati; Sunarwidhi, Anggit Listyacahyani (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Sargassum sp. is an abundant source of bioactive non-polar compounds, however their anti-bacterial potential remains understudied. This study aimed to compare the anti-bacterial activity between the methanol extract and non-polar fraction of Sargassum sp. Extraction was performed using sonication with methanol, followed by partition with petroleum ether and fractionation on silica gel G60 using n-hexane:ethyl acetate (9:1). FTIR analysis characterized the functional groups, while anti-bacterial evaluation was performed using the disc diffusion method against Staphylococcus aureus. Data were analyzed statistically using one-way ANOVA. FTIR spectrum of the methanol extract showed absorption bands corresponding to non-polar compounds. In the non-polar fraction, the bands were more dominant, suggesting a higher content of non-polar compounds. Anti-bacterial evaluation of Sargassum sp., methanol extract and non-polar fraction exhibited inhibitory effects against S. aureus. The non-polar fraction produced a larger inhibition zone compared to the methanol extract, indicating stronger anti-bacterial activity and significant difference between the two samples (p<0.05). The results of this study showed that the non-polar fraction of Sargassum sp. methanol extract has higher anti-bacterial activity compared to the extract. Further studies are recommended to elucidate the individual bioactive compounds and identify their anti-bacterial mechanisms.